2019
DOI: 10.1039/c9sc01723b
|View full text |Cite
|
Sign up to set email alerts
|

Structure of formylglycine-generating enzyme in complex with copper and a substrate reveals an acidic pocket for binding and activation of molecular oxygen

Abstract: The substrate-bound formylglycine generating enzyme forms a trigonal planar tris-thiolate Cu(i) complex ready for oxygen activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 58 publications
2
33
1
Order By: Relevance
“…In a complementary experiment we examined the structure of tc FGE in which at least 98 % of Cu I is replaced with Ag I , as inferred by X‐ray fluorescence spectroscopy (Figure S6). The tc FGE:Ag I :S complex crystallizes in the same crystal form, and adopts exactly the same structure (structure 4 ) as tc FGE:Cu I :S ( 0 ), confirming the conclusion based on NMR spectroscopy that Ag I is a reliable structural substitute for Cu I in the resting state of FGE [14] . Soaking of tc FGE:Ag I :S with O 2 or NO again formed structures ( 5 and 6 ) that are indistinguishable from their copper‐containing analogs ( 1 and 3 , Figure 2).…”
Section: Resultssupporting
confidence: 72%
“…In a complementary experiment we examined the structure of tc FGE in which at least 98 % of Cu I is replaced with Ag I , as inferred by X‐ray fluorescence spectroscopy (Figure S6). The tc FGE:Ag I :S complex crystallizes in the same crystal form, and adopts exactly the same structure (structure 4 ) as tc FGE:Cu I :S ( 0 ), confirming the conclusion based on NMR spectroscopy that Ag I is a reliable structural substitute for Cu I in the resting state of FGE [14] . Soaking of tc FGE:Ag I :S with O 2 or NO again formed structures ( 5 and 6 ) that are indistinguishable from their copper‐containing analogs ( 1 and 3 , Figure 2).…”
Section: Resultssupporting
confidence: 72%
“…However, an increase in the activity of FGE after in vitro reconstitution with Cu 2+ , led to the proposal that FGE utilizes copper as a cofactor [40][41][42]. Recently, the crystal structures of two prokaryotic FGE-holoenzymes reconstituted with Cu from Streptomycis coelicolor and Thermomonospora curvata were reported [43,44]. Both structures revealed that a Cu(I) atom is coordinated by two active site cysteine residues in a nearly linear geometry, unusual for copper-dependent oxidases.…”
Section: Fge the Msd Proteinmentioning
confidence: 99%
“…This coordination mode is unusual for O 2 ‐activating enzymes but is reminiscent of high‐affinity copper chaperones that stabilize copper as Cu I [1a, 13] . More recently, we also crystallized tc FGE in complex with Cu I and a peptide substrate ( tc FGE:Cu I :S, 1.04 Å, PDB: 6S07, substrate: Abz‐ATTPL C GPSRASILSGR, Abz: o‐aminobenzoic acid) [14] . This structure showed that the cysteine of the substrate joins the coordination sphere forming a tris‐thiolate copper complex with trigonal planar geometry (structure 0 , Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“… Panel 1 and 2: Active site view of tc FGE:Cu I :S (structure 0 ), [14] tc FGE:Cu I :S:O 2 ( 1 a ), tc FGE:Cu I :NO ( 3 ), tc FGE:Ag I :S ( 4 ), tc FGE:Ag I :S:O 2 ( 5 ), and tc FGE:Ag I :S:NO ( 6 ). 2 m|F o |−D|F c | maps are contoured at σ‐level=1.2.…”
Section: Introductionmentioning
confidence: 99%